Sikap Kekristenan terhadap Perang dan Perdamaian: Suatu Tinjauan Teologis Etis - Benyamin F Intan (Reformed Center for Religion and Society, 2022)
Looking at the relationship between war and religion, there are at least three popular ethical positions, namely holy war, pacifism, and just war. All three of them have their manifestations, both in Scripture and in church history,that rely on their logic, and produce their inadequacy. This article attempts to explore them in order to give insight into Christian thinking about war. By using a normative ethical approach, this article concludes that the position of pacifism and Just War are the options that can be taken. Furthermore, the two positions do not mutually negate each other but complementarily fill in the insufficiency of ethical questions about war in the two ethical positions.